Bullying baseline and safe and inclusive campus climate task force for the prevention and handling of violence in higher education (PPKPT task force) - Tri Nathalia Palupi; Hayati Hayati; Tsania Ilya Puspa Ayu (Indonesian Institute for Counseling, Education and Theraphy, 2026)
The Bullying Baseline Survey and Safe & Inclusive Campus Climate Survey at Borobudur University were conducted to assess new students’ experiences of violence, knowledge of violence prevention mechanisms, attitudes toward violence, perceptions of campus safety, and expectations for a safe learning environment. Using a descriptive quantitative cross-sectional design, data were collected from 192 first-year students participating in the 2025 Student Orientation Program (PKKMB). The findings revealed that 54% of respondents had experienced or witnessed at least one form of bullying or unhealthy relationship before entering university, with cyberbullying (88%) and physical violence among students (62%) being the most frequently reported experiences. Respondents demonstrated high levels of knowledge regarding the Prevention and Handling of Violence in Higher Education (PPKPT) system (M=4.44), positive anti-violence attitudes (M=4.57), strong perceptions of campus safety (M=4.53), and high expectations for violence prevention initiatives (M=4.67). The study highlights the need to strengthen support services, reporting mechanisms, and counseling programs to foster a safe, inclusive, and equitable campus environment.